Diazotrophs for Lowering Nitrogen Pollution Crises: Looking Deep Into the Roots - Imran, Asma; Hakim, Sughra; Tariq, Mohsin; Nawaz, Muhammad Shoib; Laraib, Iqra; Gulzar, Umaira; Hanif, Muhammad Kashif; Siddique, Muhammad Jawad; Hayat, Mahnoor; Fraz, Ahmad; Ahmad, Muhammad (Frontiers in Microbiology, 2021)
The extensive use of agrochemicals especially nitrogen (N) during and after green revolution in the last century although resulted in a remarkable increase in crop yield but has drastically reduced soil fertility, increased the production cost, food prices, carbon footprints, depleted the fossil reserves with huge penalties to environment and ecological sustainability. The ground water, rivers and oceans are loaded with the excessive N which is an environmental catastrophe. Nitrogen emissions (e.g., ammonia, nitrogen oxide, nitrous oxide) play an important role in global climate change and contribute to particulate matter, acid rain causing respiratory problems, cancers, damage to forests and buildings. The nitrogen-soaked planet Earth needs concerted global efforts to avoid the disaster in future. Efforts to improve agricultural N management focus on synchronization of crop N-demand and N-supply along with improving the N-use efficiency of the crops. However, these is a very little focus on the natural sources of N available for plants in the form of diazotrophic bacteria present inside or on the root surface. These diazotrophs are the mini-nitrogen factories that convert excessively available (78%) atmospheric N2 to ammonia through a process known as “biological nitrogen fixation” which is then taken up by the plants for its metabolic functioning. Diazotrophs also stimulate root architecture by producing plant hormones hence improve overall plant’s ability to uptake nutrient and water. Moreover, nanotechnology has revolutionized the whole industry. Nano-fertilizers and coated slow-releasing fertilizers are being formulated that have less problem of volatilization and leaching. With this in mind, the review explores the following questions; To what extent the crop N-requirements be met by diazotroph inoculation? And can N-input to agriculture be managed in such a way that environment benefits, farmers save money and the fertilizer industry profits? A future roadmap to decrease nitrogen inputs to the agricultural system is also described.